(untitled) (Journal of the College of Basic Education, 2023)
This research dealt with the term endowment, which is considered one of the phonetic terms for our Muslim scholars from among the readers and linguists. Appropriate in revealing the content of this indication and its connection to the endowment positions.Our research included six important terms on the subject of waqf, and we dealt in detail with each of them in two sections, namely:The first: (Al-Mufassal, the endowment, the silence, the pieces, the parts of the endowment), and the second: (the indications of transformation in the endowment).